2022
DOI: 10.29244/jcfcs.1.3.196-208
|View full text |Cite
|
Sign up to set email alerts
|

Marital Adjustment, Gender Role Partnerships, and Marital Satisfaction During Covid-19

Abstract: During the Covid-19 pandemic, orders to work and study from home became a problem for families in Indonesia. Marital adjustment and gender role partnerships in the household must be well established to create marital satisfaction so that there is no conflict in the family. This study analyzes the factors influencing marital satisfaction in intact families during the Covid-19 pandemic. Respondents in this study are wives from intact families who have children and are domiciled in the city of Bogor. The sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The condition of the husband who works as a servant of the congregation with a solid work time, coupled with an unbalanced domestic labor division and the demands of the wife to assist the husband's services, can be accepted and carried out by the wife. This aligns with the results of research conducted by Tazkiya and Puspitawati (2022), which reveals that marriage adjustments have a significant positive relationship with marriage satisfaction-the higher the marriage adjustment, the higher the marriage satisfaction created in the family.…”
Section: Marriage Adjustment Effect On Marriage Satisfactionsupporting
confidence: 87%
See 1 more Smart Citation
“…The condition of the husband who works as a servant of the congregation with a solid work time, coupled with an unbalanced domestic labor division and the demands of the wife to assist the husband's services, can be accepted and carried out by the wife. This aligns with the results of research conducted by Tazkiya and Puspitawati (2022), which reveals that marriage adjustments have a significant positive relationship with marriage satisfaction-the higher the marriage adjustment, the higher the marriage satisfaction created in the family.…”
Section: Marriage Adjustment Effect On Marriage Satisfactionsupporting
confidence: 87%
“…Rachmawati and Mastuti (2013) revealed that based on their study, wives with a high marriage adjustment generally have a higher level of marriage satisfaction than those with a moderate marriage adjustment show differences in the level of marriage satisfaction. Thus, adjustments in marriage have a significant role in marriage satisfaction (Anjani & Suryanto, 2006;Atwater & Duffy, 2009in Retiara et al, 2016Tazkiya and Puspitawati (2022),).…”
Section: Introductionmentioning
confidence: 99%
“…Couples with lower incomes tend to predict lower marital satisfaction and experience more psychological pressure than couples with more financial resources. Tazkiya & Puspitawati (2022) in their study, also noted that a higher husband's income is associated with higher marital satisfaction. The consequence of low marital satisfaction among couples with low incomes is an increased vulnerability to divorce.…”
Section: Discussionmentioning
confidence: 73%
“…So, to achieve satisfaction in marriage, married couples must continually readjust their understanding of what is expected of each other in their roles [22] The same results were stated by Abbas and Nadhirah that there is a significant correlation between marital adjustment and marital satisfaction [1,17]. Different results were expressed by Tazkiya & Puspawati that there was an indirect effect between marital adjustment and marital satisfaction; the gender role variable mediated the relationship between these two variables [29].…”
Section: Introductionmentioning
confidence: 78%